2021
DOI: 10.28991/scimedj-2021-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impacts of Chronic Kidney Disease and Dialysis Therapy

Abstract: Background: Chronic Kidney Disease (CKD) has been a significant global health problem and a source of an enormous burden on the healthcare system and psychological distress for diagnosed patients. This study aims to understand the psychosocial impacts of CKD and dialysis therapy on patients undergoing dialysis in LAUTECH Teaching Hospital, Osogbo. Methodology: A descriptive study design was used, and the sampling technique was purposive. Subject participation was voluntary and preceded informed consent. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(1) integrating health literacy initiatives into existing corporate social responsibility programs focused on health and wellbeing in the workplace; (2) engaging in an active dialogue with key healthcare stakeholders; and (3) developing a -Blueprint for Action in Health Literacy,‖ based on best practices and case studies. Companies and programs that are moving toward enhancing their social role in society will be able to solve many problems by assessing the current organizational health literacy responsiveness situation of healthcare organizations, knowing and arranging the different areas and weaknesses of health literacy in organizations according to the sustainable development priorities of the health sector, and focusing on these points and creating partnerships between health institutions and the institutions.…”
Section: B the Corporate Social Responsibility Sustainable Development And Health Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…(1) integrating health literacy initiatives into existing corporate social responsibility programs focused on health and wellbeing in the workplace; (2) engaging in an active dialogue with key healthcare stakeholders; and (3) developing a -Blueprint for Action in Health Literacy,‖ based on best practices and case studies. Companies and programs that are moving toward enhancing their social role in society will be able to solve many problems by assessing the current organizational health literacy responsiveness situation of healthcare organizations, knowing and arranging the different areas and weaknesses of health literacy in organizations according to the sustainable development priorities of the health sector, and focusing on these points and creating partnerships between health institutions and the institutions.…”
Section: B the Corporate Social Responsibility Sustainable Development And Health Literacymentioning
confidence: 99%
“…This framework could be used in general or as a specific framework. The following are required: (1) To achieve a good picture of the importance of health literacy criteria from the sustainable perspective of the country, the healthcare sustainable conditions in its different areas and the role of the selected healthcare facility in achieving it should be considered; (2) The importance of the criteria is deferent by cities and healthcare facility types (hospital, unit, or center and public or private), and this deference should also be considered; (3) The investigated and compared healthcare organizations should be located at the same location, and have the same facility type; (4) The selected indicators should be applicable for use in the selected sector [10]; (5) The information gathering should be repeatable and stable, and the consistency test for the data gathered should use fuzzy analytic hierarchy process data, and an agreement test for the decision makers' opinions gathered using fuzzy Delphi should be performed; and (6) The framework should allow the healthcare sector or companies to visualize and explain the results of the evaluation, weighting, and comparison and, finally, allow a derivation of the areas where the government or companies could improve or where the business sector could help, serve, or plan its corporate social responsibility practices.…”
Section: A Requirements Of the Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…in China [ 8 ]. In recent decades, several major diseases including cardiovascular diseases, chronic kidney diseases and neurodegenerative diseases have been significant health problems globally [ 9 , 10 ]. Recently, a series of studies showed that Fuzi products including Hei-Shun-Pian, Bai-Fu-Pian and other traditional Chinese medicines had anti-inflammatory and immune-enhancing effects in such major diseases.…”
Section: Introductionmentioning
confidence: 99%